Workplace ostracism and employee wellbeing: A conservation of resource perspective - Wang, Long-mei; Lu, Lei; Wu, Wei-lin; Luo, Zi-wei (Frontiers in Public Health, 2023)
As a common phenomenon of workplace ostracism in corporate management, it is urgent to clarify how it affects employee well-being. Based on Conservation of Resource Theory, this study investigates the mechanisms of workplace ostracism on employee well-being and examines the mediating role of emotional exhaustion and the moderating role of team forgiveness climate by surveying 282 employees from 68 companies in mainland China. The results show that (1) workplace ostracism negatively affects employee well-being; (2) emotional exhaustion plays a mediating role between workplace ostracism and employee well-being; (3) team forgiveness climate weakens the negative effect of workplace ostracism on emotional exhaustion and negatively moderates the indirect effect of workplace ostracism on employee well-being through emotional exhaustion. It tries to provide theoretical basis and practical guidance for eliminating the negative effects of workplace ostracism and focusing on employee well-being.